Understanding the cyclic performance of composite steel-concrete connections on steel bridges. (1st December 2020) - Rahnavard, Rohola; Rebelo, Carlos; Craveiro, Hélder D.; Napolitano, Rebecca
Highlights: 17 FE models of steel bridges with welded and composite connections were created. Static cyclic and dynamic time history analysis were applied. The results suggest that the composite connection would increase dissipated energy. Abstract: This paper describes a numerical study using the finite element method to evaluate the seismic performance of composite steel-concrete connections designed to protect critical welded interface areas between the steel pipe pile and cap beam bridge piers. Previous studies have indicated that welding the steel piles directly to a steel cap beam, regardless of weld configuration, does not avoid the undesirable brittle cracking failure mode in the welded region. Strengthening of the connection can a solution to shift the plastic hinge position from the connection to another point of the structure. Through static pushover and time-history analysis, the connection has been shown to adequately extend plastic hinging in the form of local buckling in the pipe pile wall, while avoiding unfavorable failure modes. The results of this study demonstrate that the use of composite connections can increase the shear capacity of a steel bridge; thus, improving its performance. Moreover, evaluation of the results shows that an increase in the length of the composite area will improve the overall ductility of the steel frame. Finally, a new composite connection has been proposed to improve the performance of the steel bridge; this will augment current efforts in strengthening bridges in earthquake-prone areas.